2003
DOI: 10.1097/01.ccm.0000089644.70597.c1
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy with a tissue-engineered kidney reduces the multiple-organ consequences of septic shock

Abstract: These results demonstrate that renal cell therapy ameliorates cardiac and vascular dysfunction, alters systemic cytokine abnormalities, and improves survival time in a large animal model of Gram-negative septic shock. A cell therapeutic approach with a tissue-engineered bioartificial kidney may be a new treatment modality for this current unmet medical need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…Plasma levels of HCO 3 Ϫ , P i , and K ϩ were maintained nearer to normal values; glucose, HCO 3 Ϫ , and K ϩ active transport as well as ammonia excretion, glutathione processing, and 25-hydroxyvitamin D 3 conversion were demonstrated (Humes et al, 1999a. Furthermore, in canine and porcine models of ARF with septic shock, RAD treatment was shown to modulate plasma cytokine levels, maintain better cardiovascular performance (as determined by cardiac output and renal blood flow), and increase survival times Humes et al, 2003).…”
Section: Full Renal Replacementmentioning
confidence: 95%
“…Plasma levels of HCO 3 Ϫ , P i , and K ϩ were maintained nearer to normal values; glucose, HCO 3 Ϫ , and K ϩ active transport as well as ammonia excretion, glutathione processing, and 25-hydroxyvitamin D 3 conversion were demonstrated (Humes et al, 1999a. Furthermore, in canine and porcine models of ARF with septic shock, RAD treatment was shown to modulate plasma cytokine levels, maintain better cardiovascular performance (as determined by cardiac output and renal blood flow), and increase survival times Humes et al, 2003).…”
Section: Full Renal Replacementmentioning
confidence: 95%
“…Candidate biological markers that are known to be dysregulated in ESRD, correlated with poor outcome and linked to known mechanisms of disease, are markers of inflammation and oxidative stress. Pre-clinical animal models of septic shock have shown that treatment with a device containing metabolically active kidney cells decreases levels of inflammatory peptides compared with a sham device [45].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and ex vivo tests of renal assist devices have been conducted of animals and critically ill patients, with promising results that include better cardiovascular and hemodynamic parameters and improved survival (18 -20). Of particular interest is the potential differential beneficial effect in patients with acute kidney injury associated with sepsis (21)(22)(23)(24)(25).…”
Section: Living Membranes and Bioartificial Kidneymentioning
confidence: 99%